PENYULUHAN TENTANG FAKTOR SIKAP IBU PADA KELENGKAPAN IMUNISASI LANJUTAN PADA ANAK USIA 18-36 BULAN DI DESA PAKONG - kurratul aini (UNIVERSITAS MITRA INDONESIA, 2022)
Immunization is one tool that parents may use to track their child's growth and development. Immunization is a method of developing immunity against infectious illnesses and disorders that may result in disability or death. Objective: The purpose of this study was to ascertain the influence of maternal attitudes on the completion of advanced vaccination in infants. Method: The cross-sectional correlational analysis was utilized in this research. Purposive sampling was used in this research, with 58 samples collected. The data were gathered via KIA books and questionnaires, with the Spearman Rank test used for statistical analysis. Results: The research discovered that the majority of respondents (72.4 percent) had received comprehensive basic vaccination and that the majority of respondents (56.9 percent) had a favorable opinion toward immunization. The findings of the Spearman Rank test give a p-value of 0.000.(0.05). Conclusion: It is well established that the majority of moms have a positive attitude about immunizing their children. Conclusion: The results indicate that the majority of responders gave comprehensive vaccinations. The findings indicated that there was a correlation between the mother's attitude and the completion of children's basic vaccination. Keywords: Attitude and follow-up immunization